'One-pot' organocatalyzed enantioselective synthesis of highly functionalized 3, 4, 5, 6-tetrasubstituted dihydropyrans by sequential Knoevenagel condensation/Michael addition and hemiacetalization. Issue 1 (15th January 2017) - Tilekar, Ajay R.; Jagdale, Arun R.; Kukreja, Gagan; Shenoy, G. Gautham; Sinha, Neelima
Graphical abstract: Simple and efficient organocatalyzed asymmetric synthesis of highly functionalized 3, 4, 5, 6-tetrasubstituted dihydropyrans has been developed. Abstract: An organocatalytic 'one-pot' synthesis of highly functionalized 3, 4, 5, 6-tetrasubstituted dihydropyrans has been developed. Excellent enantio- and diastereo selectivity with good yields are some of the salient features of this methodology. This reaction takes advantage of proline based catalysts and follows stepwise sequential transformations including Knoevenagel condensation–Michael addition–hemiacetalization towards the synthesis of complex dihydropyranol framework. Abstract : Ethyl (3 R, 4 R )-4-ethyl-3-methyl-2-oxo-6-phenyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C17 H20 O4 [ α ]D 23  = +20.2 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-3-methyl-6-(4-nitrophenyl)-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C17 H19 NO6 [ α ]D 23  = +21.8 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-6-cyclopropyl-4-ethyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C14 H20 O4 [ α ]D 25  = +30.0 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-6-cyclopropyl-3-ethyl-2-oxo-4-propyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C16 H24 O4 [ α ]D 23  = +29.8 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-6-isopropyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C14 H22 O4 [ α ]D 23  = +20.7 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-3, 6-dimethyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C12 H18 O4 [ α ]D 23  = +28.1 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-3-ethyl-6-methyl-2-oxo-4-propyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C14 H22 O4 [ α ]D 24  = +25.6 ( c 0.41, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-butyl-6-methyl-2-oxo-3-propyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C16 H26 O4 [ α ]D 24  = +50.0 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4, 6-diethyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C13 H20 O4 [ α ]D 23  = +26.3 ( c 0.41, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-3-methyl-6-(4-nitrophenyl)-2-oxo-4-(thiophen-3-yl)-3, 4-dihydro-2 H -pyran-5-carboxylate: C17 H19 NO6 S [ α ]D 24  = +42.4 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-6-cyclopropyl-3-methyl-2-oxo-4-(thiophen-3-yl)-3, 4-dihydro-2 H -pyran-5-carboxylate: C16 H18 O4 S [ α ]D 24  = +128.4 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 S )-3-ethyl-4-(3-fluorophenyl)-6-isopropyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C19 H23 FO4 [ α ]D 24  = +104.4 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 S ) Abstract : Ethyl (3 R, 4 S )-3, 6-dimethyl-2-oxo-4-phenyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C16 H18 O4 [ α ]D 25  = +107.9 ( c 0.41, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 S ) Abstract : (3 R, 4 R )-6-( tert -Butyl)-4-ethyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carbonitrile: C13 H19 NO2 [ α ]D 24  = +43.1 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organoctalyst Absolute configuration: (3 R, 4 R ) Abstract : (3 R, 4 R )-3-Ethyl-2-oxo-6-phenyl-4-propyl-3, 4-dihydro-2 H -pyran-5-carbonitrile: C17 H19 NO2 [ α ]D 24  = +46.8 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : (3 R, 4 R )-4-Butyl-2-oxo-6-phenyl-3-propyl-3, 4-dihydro-2 H -pyran-5-carbonitrile: C19 H23 NO2 [ α ]D 25  = +17.6 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-3-methyl-2-oxo-6-(( E )-styryl)-3, 4-dihydro-2 H -pyran-5-carboxylate: C19 H22 O4 [ α ]D 24  = +32.0 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-3-butyl-2-oxo-4-pentyl-6-(( E )-styryl)-3, 4-dihydro-2 H -pyran-5-carboxylate: C25 H34 O4 [ α ]D 24  = +52.7 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-6-(( E )-4-fluorostyryl)-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C19 H21 FO4 [ α ]D 23  = +35.5 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-6-(( E )-4-cyanostyryl)-4-ethyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C20 H21 NO4 [ α ]D 23  = +58.4 ( c 0.1, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-6-(( E )-4-methoxystyryl)-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C20 H24 O5 [ α ]D 24  = +17.1 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-3-methyl-6-(( E )-4-nitrostyryl)-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C19 H21 NO6 [ α ]D 23  = +51.0 ( c 0. 1, CHCl3 ) Source of chirality: the precursor Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-3-ethyl-6-(( E )-4-nitrostyryl)-2-oxo-4-propyl-3, 4-dihydro-2 H -pyran-5-carboxylate: C21 H25 NO6 [ α ]D 25  = +40.8 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ethyl (3 R, 4 R )-4-ethyl-3-methyl-2-oxo-6-(( E )-2-(thiophen-3-yl)vinyl)-3, 4-dihydro-2 H -pyran-5-carboxylate: C17 H20 O4 S [ α ]D 23  = +68.7 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : Ehyl (3 R, 4 R )-6-(( E )-but-1-en-1-yl)-4-ethyl-3-methyl-2-oxo-3, 4-dihydro-2 H -pyran-5-carboxylate: C15 H22 O4 [ α ]D 25  = +90.0 ( c 0.5, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (3 R, 4 R ) Abstract : (4 R, 5 S )-5-Ethyl-4-methylcyclohex-2-en-1-one: C9 H14 O [ α ]D 21  = +58.1 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (4 R, 5 S ) Abstract : (4 R, 5 S )-5-Butyl-4-propylcyclohex-2-en-1-one: C13 H22 O [ α ]D 23  = +172.0 ( c 1.0, CHCl3 ) Source of chirality: asymmetric organocatalyst Absolute configuration: (4 R, 5 S )